2012
DOI: 10.1136/vr.100304
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii in bulk tank milk samples from dairy goat and dairy sheep farms in The Netherlands in 2008

Abstract: In 2007, a human Q fever epidemic started, mainly in the south eastern part of The Netherlands with a suspected indirect relation to dairy goats, and, to a lesser degree, to dairy sheep. This article describes the Q fever prevalences in Dutch dairy goat and dairy sheep bulk tank milk (BTM) samples, using a real-time (RT) PCR and ELISA. Results of BTM PCR and ELISA were compared with the serological status of individual animals, and correlations with a history of Q fever abortion were determined. When compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 21 publications
(36 reference statements)
2
54
0
Order By: Relevance
“…Before the start of the vaccination campaign in 2008, BTM ELISA results showed that 87 (29.8%) out of 292 voluntarily submitted BTM samples from dairy goat farms were serologically positive ( Van den Brom et al, 2012b). Our study shows that within a year after vaccination BTM ELISA results were significantly higher compared with the period before.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Before the start of the vaccination campaign in 2008, BTM ELISA results showed that 87 (29.8%) out of 292 voluntarily submitted BTM samples from dairy goat farms were serologically positive ( Van den Brom et al, 2012b). Our study shows that within a year after vaccination BTM ELISA results were significantly higher compared with the period before.…”
Section: Discussionmentioning
confidence: 51%
“…In this retrospective cohort study, 28% of all dairy goat farms tested C. burnetii BTM PCR positive in at least 1 of the first 3 rounds of the surveillance program in 2009. Compared with 2009, a slightly higher proportion of dairy goat farms was BTM PCR positive in 2008 (32.9%; 95% CI = 30.2-35.6), although that prevalence was measured in voluntarily submitted BTM samples from 74.4% of the Dutch dairy goat farms (Van den Brom et al, 2012b). As surveillance programs for C. burnetii based on BTM samples from dairy goat farms are a relatively new phenomenon, only a small number of studies from other countries described results of C. burnetii BTM testing.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In a study performed in Germany, C. burnetii DNA was found in 5% of 39 flock's sheep 27 . In the Netherlands, C. burnetii DNA was detected in 33% of 292 goat farms 28 . In Italy, C. burnetii DNA was amplified in 18% of 199 goats and sheep farms with reproductive history 29 .…”
Section: Discussionmentioning
confidence: 99%